Livro de artista: criações e proposições de ensino - Barcelos, Lana Issa dos Santos (2023)
The research entitled “Artist's book: creations and teaching propositions”, has as the guiding question of the investigation to question: how to mediate the process of creating an artist's book with my students in the classroom? The general objective of the study is to comparatively outline methodologies of creation processes of artist's books, experimented with children of the fourth year of elementary school and by the teacher- researcher. And with the specific objective, reflectively describe the different practices and methodologies from three reference artists, Bruno Munari, Lygia Clark and Hélio de Lima. Regarding methodological issues, this research is based on the phenomenological method, based on the perspective of Merleau-Ponty (2018), through a qualitative approach and with emphasis on the studies of Ludke and André (1986). This work sought to contribute to teachers in the classroom, pointing out possibilities for working with the production of an artist's book, thinking of this book as a work of art, a playful object, a learning tool or a teaching strategy.